The adaptability of Islamic Criminal Values to The Reformulation of Corruption Criminal Sanctions in Indonesia from Human Rights Perspective - Rahman, Fathor; Luth, Thohir; Madjid, Abdul; Noerdajasakti , Setiawan (Technium Social Sciences Journal, 2021)
Islamic criminal law values related to the formulation of sanctions against perpetrators of criminal acts of corruption have an open opportunity and a way to be used as a reference in reforming criminal sanctions for corruption in Indonesia. However, so far, they still find a dead end because they are confined by understanding Islamic law’s textualism. They want the application of Islamic criminal law purely under the texts. This research answers how the transformation of Islamic criminal law values in understanding contextualism through legal hermeneutics. There are forms of punishment that suit the needs and can be adaptively accepted by the community. Indonesia. The object of this study is the formulation of criminal sanctions for corruption in Islamic criminal law through the method of reorienting the thought of Islamic criminal law, based on the concept of "maqasyid al-syar’iyah" which is universally accepted by all Indonesian people because in this study it aims to position the sanctions. Islamic punishment as an alternative sanction in the framework of reformulation of the criminal sanctions of corruption in Indonesia by still considering human rights values, so that reformulation of criminal sanctions for corruption in Indonesia can achieve the main objective of the law, namely to create problems for human life, both in the world and in the hereafter.